Distorted Perceptions of Body weight: Examining Body Image Dissatisfaction and Psychological Distress in Adolescents - Dr. Mussarat Anwar; Dr. Shahid Iqbal; Dr. Ayesha Anwar; Ms Ayesha Ijaz, (Dialogue Social Science Review (DSSR), 2025)
This study explores the relationship between body weight perception, psychological distress, and weight management behaviors among adolescents in Peshawar, Pakistan. Using a cross-sectional design, data were collected from 200 adolescents (100 males, 100 females), aged 13–19, through stratified random sampling. Participants' body weight perception was assessed using Stunkard’s Figure Rating Scale, while psychological distress was measured with the Kessler Psychological Distress Scale (K10). A structured questionnaire gathered information on BMI, dietary habits, and weight management strategies. The study found that 80.5% of participants misperceived their body weight, with females more likely to overestimate and males to underestimate their body size. Adolescents with distorted body image perceptions experienced significantly higher levels of psychological distress and were more likely to engage in unhealthy weight management practices, such as meal skipping and extreme dieting. Gender differences were evident, with females demonstrating more significant body dissatisfaction and emotional distress. These findings underscore the need for culturally sensitive interventions to address body image misperceptions and promote mental health among Pakistani adolescents.